Reconfiguring Education Systems in the 21st Century: Innovation, Equity, and Global Transformation - Saefullah, Selvia Ruyatus; Hadian, Mohamad Heri; Hendriawan, Erry; Krismayanti, Yanti; Adiningsih, Neni Utami (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the reconfiguration of education systems in the 21st century by emphasizing the interconnected roles of innovation, equity, and global transformation. The research employs a qualitative approach with a literature-based design to analyze contemporary educational shifts through academic publications and official government data. The findings reveal that educational innovation, particularly through digital technology integration and adaptive pedagogical models, serves as a primary catalyst for systemic transformation. However, disparities in access remain evident, as indicated by the significant decline in school participation rates from 99.19% among children aged 7–12 to 29.01% among young adults aged 19–23 in Indonesia, highlighting structural challenges in sustaining educational continuity. The study further identifies that global transformation has reshaped educational priorities, requiring institutions to incorporate 21st-century competencies, including critical thinking, digital literacy, and cross-cultural understanding. Despite progress in digital adoption, unequal infrastructure distribution and varying levels of institutional readiness continue to hinder inclusive implementation. The discussion underscores that successful education system reconfiguration requires a holistic and integrated approach involving policy alignment, capacity building, and technological accessibility. The study concludes that an adaptive, inclusive, and innovation-driven education system is essential for enhancing global competitiveness while reducing social inequalities. These findings contribute to the broader discourse on sustainable education development by providing a conceptual and empirical foundation for policymakers and educational institutions to design resilient and future-oriented systems.